2023
DOI: 10.1007/s10207-023-00676-0
|View full text |Cite
|
Sign up to set email alerts
|

From zero-shot machine learning to zero-day attack detection

Abstract: Machine learning (ML) models have proved efficient in classifying data samples into their respective categories. The standard ML evaluation methodology assumes that test data samples are derived from pre-observed classes used in the training phase. However, in applications such as Network Intrusion Detection Systems (NIDSs), obtaining data samples of all attack classes to be observed is challenging. ML-based NIDSs face new attack traffic known as zero-day attacks that are not used in training due to their non-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Further investigation revealed that these assaults with low-zero-day detection percentages have distinctive characteristic distributions and a wider Wasserstein distance than assaults in other assault classes. These results show the need to consider certain feature distributions to overcome such obstacles and illustrate the shortcomings of ML-based IDSs in successfully identifying specific zero-day attack situations [24].…”
Section: Related Literaturementioning
confidence: 92%
See 1 more Smart Citation
“…Further investigation revealed that these assaults with low-zero-day detection percentages have distinctive characteristic distributions and a wider Wasserstein distance than assaults in other assault classes. These results show the need to consider certain feature distributions to overcome such obstacles and illustrate the shortcomings of ML-based IDSs in successfully identifying specific zero-day attack situations [24].…”
Section: Related Literaturementioning
confidence: 92%
“…To evaluate the effectiveness of machine learning-based IDSs in recognizing zeroday attack scenarios, Sarhan et al [24] developed a unique zero-shot learning approach. The learning models translate data characteristics to semantic attributes that distinguish between known attacks and benign activity during the attribute learning step.…”
Section: Related Literaturementioning
confidence: 99%
“…In a similar vein, Kumar, V. developed a two-phase intelligent network technique specifically for identifying zero-day threats, achieving impressive accuracy rates of over 90% on CICIDS 2018 and real-time datasets using created signatures [25]. Sarhan, M. suggested a zero-sample learning technique to evaluate the performance of machine learning-based detection systems against unknown threats, providing valuable insights into their abilities to identify and mitigate such threats [26]. Sheng, C. devised a self-growing attack traffic classification system based on density-based heuristic clustering to improve the detection of unknown forms of attacks, enabling real-time automated detection [27].…”
Section: Related Workmentioning
confidence: 99%
“…The findings conclude that SVM, scoring an average accuracy of 98.18%, refers to the best machine learning algorithm that can detect intrusions in a system. To empower machine learning-based NIDS to be able to detect zero-day attacks, [7] proposes a zero-shot learning method, which maps network data to known and unknown attack behaviors. Designing zero-day detection rate, the study was able to measure the effectiveness of the ML model developed, using UNSW-NB15 and NF-UNSW-NB15v2 datasets.…”
Section: Related Workmentioning
confidence: 99%
“…With the widespread usage of Internet applications, numerous network security issues occur on a regular basis, weakening network security. The vulnerabilities in cyberspace have led to various cyber-attacks including unauthorized access, denial of service (DoS), malware attacks, zero-day attacks, data breaches, social engineering, or phishing [5]- [7]. In May 2017, a ransomware virus caused massive losses in several areas, including banking, energy, medical care, and colleges.…”
Section: Introductionmentioning
confidence: 99%